2018
DOI: 10.1038/s41419-017-0139-8
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 modulation influences human neural stem cell proliferation and differentiation

Abstract: Toll-like receptor 4 (TLR4) activation is pivotal to innate immunity and has been shown to regulate proliferation and differentiation of human neural stem cells (hNSCs) in vivo. Here we study the role of TLR4 in regulating hNSC derived from the human telencephalic-diencephalic area of the fetal brain and cultured in vitro as neurospheres in compliance with Good Manifacture Procedures (GMP) guidelines. Similar batches have been used in recent clinical trials in ALS patients. We found that TLR2 and 4 are express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 32 publications
7
27
0
7
Order By: Relevance
“…Mammalian TLRs have relevant roles in embryogenesis, development of neurons and neural circuits, learning and memory, with regulatory roles on the processes of proliferation, differentiation, outgrowth, plasticity and neuron survival (Rolls et al, 2007; Shechter et al, 2008; Hanke and Kielian, 2011; Okun et al, 2011; Barak et al, 2014; Grasselli et al, 2018). Thus, it is expected that TLRs contribute to the development and maintenance of retinal structure and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian TLRs have relevant roles in embryogenesis, development of neurons and neural circuits, learning and memory, with regulatory roles on the processes of proliferation, differentiation, outgrowth, plasticity and neuron survival (Rolls et al, 2007; Shechter et al, 2008; Hanke and Kielian, 2011; Okun et al, 2011; Barak et al, 2014; Grasselli et al, 2018). Thus, it is expected that TLRs contribute to the development and maintenance of retinal structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…It is now evident that, far from their primary well-known function as mediators of the immune response, TLRs play additional relevant roles in the progression of different pathological conditions, such as non-infectious neuronal injuries and neurodegenerative disorders (Carty and Bowie, 2011; Hanke and Kielian, 2011; Okun et al, 2011; Feldman et al, 2015). Interestingly, recent findings show that TLRs also appear to be involved in many physiological cellular processes, such as the development of neuronal circuits during embryogenesis, progenitor cell proliferation and differentiation, CNS plasticity throughout the entire life or drug-reward behavior (Rolls et al, 2007; Shechter et al, 2008; Okun et al, 2011; Barak et al, 2014; Kashima and Grueter, 2017; Grasselli et al, 2018). So far, numerous endogenous TLR ligands have been identified that could play a role in the regulation of CNS physiological processes and in the development and progression of neurodegenerative disorders (Trotta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 expression was observed on neural progenitors in the retina, and the activation of TLR4 decreased cell proliferation and induced the differentiation of progenitors into neurons [ 160 ]. Human NSCs express both TLR2 and TLR4, which decreased upon differentiation [ 161 ]. TLR4 inhibition decreased human NSC proliferation, while its activation increased differentiation rates [ 161 ].…”
Section: Multiple Ha Receptors Respond To Ha In the Developing Mamentioning
confidence: 99%
“…Human NSCs express both TLR2 and TLR4, which decreased upon differentiation [ 161 ]. TLR4 inhibition decreased human NSC proliferation, while its activation increased differentiation rates [ 161 ].…”
Section: Multiple Ha Receptors Respond To Ha In the Developing Mamentioning
confidence: 99%
“…TLR signaling has been shown to play a role in regulating differentiation of several cell types, including human neural stem cells, 30 and immunity-related cells like T-cells, B-cells, 31,32 and macrophages. 33 In MSCs, Pevsner-Fischer and colleagues showed that TLRs and their ligands can serve as a regulator of MSC proliferation and differentiation.…”
Section: Soluble Alternan Does Not Inhibit Osteogenic and Adipogenic mentioning
confidence: 99%